Perception cultural expressions of knowledge and integrated promotion in the Andean community, Caraz Ancash, Peru - Paredes T., Mildred (2009)
Cultural expressions belonging to a particular subject area reflect the diversity of cultural identities by linking content, values and lifestyles (UNESCO, 2005), to develop goods and services would enable socio-economic inclusion of the Peruvian Andean peasant communities with products for a market potential is still existing in the study area. Problem: Which is the effect of the application of the workshop on the added value of the cultural products in inhabitants of small villages of the Comunidad Campesina Cruz de Mayo of Caraz, Ancash? In the meantime the inhabitants of two groups of houses are ignorant of that these products would be able to have value aggregation for the Peasant Community Cruz de Mayo of Callejón de Huaylas, Caraz, Ancash. Applied research, cuasiexperimental design; Previously scanned and posted the feasible products of cultural expressions, applying over oneself Perception’s ladder of 20 items with four grades of assessment; Reliability: 0.90 and validity of contents for opinion of judges and capability of discrimination. Hypothesis: The workshop on added value found the perception of the cultural products for his commercialization in residents of the community Cruz de Mayo, Ancash. Result: H1, since sensible decrease in the perception of the application of added value had the cultural products accepts the alternating hypothesis himself. (t= - 2,19 to the 0.05).